Percepção dos moradores ribeirinhos da comunidade Ilha de Santa Luzia, em Mossoró/RN (trecho do rio Apodi-Mossoró), e dos profissionais de saúde acerca do acesso aos serviços de saúde no âmbito da UBS Antônio Camilo - Silva, José Thallys Moreira da (Universidade Federal Rural do Semi-Árido, 2020)
The thematic access is multi-meaning and directly impacts the quality of Primary Health Care, a fact that promotes the concern of the present study about the structural and socioenvironmental factors that make it difficult for the riverside people to access health services provided by the Antônio Camilo Basic Health Unit. Thus, this paper aims to evaluate access from the perspective of riverine users and health professionals. As specific objectives, we have: capture the structural difficulties in the perception of patients and professionals that prevent the full access of the riparian to health care, comparing it to those of other locations; Identify the existing understanding, from the perception by users and professionals, about what is considered health access; analyze, in the view of health professionals, the determinants of access and the actions taken to mitigate possible difficulties. The present study was developed in the city of Mossoró / RN, through a descriptive field research with qualitative approach, being recorded in audio. Allied to the interviews, the researchers used participant observation with notes in a field diary. The research population consisted of riverine residents of the Apodi-Mossoró River stretch, assigned by UBS Antônio Camilo and health professionals from the same locality, with a sample of 13 users and 4 professionals. The research was carried out rigorously, following the ethical and bioethical precepts ensured by the resolutions 466/2012 of the National Health Council. The study was developed soon after it was approved by the UERN Research Ethics Committee, according to the opinion number 08312819.5.0000.5294. The participants of the study were explained the objectives of the research and, afterwards, were held the interview. With regard to data analysis, we used Bardin's Content Analysis. Difficulties in access were observed due to the appointment of appointments with medical specialties, waiting time of about 2 years; the geographical barrier of the Apodi-Mossoró River, especially for the population that lives not adjacent to the health post; difficulties regarding access to medications; problems related to reception directly influencing the access to services of the unit; little or no perception of the expanded concept of health by users interviewed; environmental difficulties arising from the presence of the Apodi-Mossoró River encountered by residents, such as flooding, disease transmission and infestation by wild animals and animals of urban origin; violence as a factor of illness and hindering access to services of the Health Unit. On the part of health professionals, a broader view of the concept of access to health was observed and the following points were identified as facilitating points of access for these peoples: the bond with the team, their needy situation, the performance of health actions and the contributions made. the medical residences in Family and Community Medicine of UERN and the multiprofessional; The following points were raised as difficulties: referrals to medical specialties, restricted view of health by users and, consequently, low self-care, besides the physical barrier of the Apodi-Mossoró River for the population not adjacent to UBS. Therefore, when assessing an atypical riparian population in the northeast interior, one may notice typical features of other traditional riparian populations, such as difficulty in accessing health services, transmission of diseases typical of those living near water sources (diarrhea, arboviruses, accidents with venomous animals, among others) and abandonment of houses during floods. On the other hand, the differences from other riparian groups were basically the non-extractive lifestyle and fishing income, and the fact that it was a socially marginalized riverine population in the center of the area. city, which suffers from the same factors as the typically urbanized area, such as violence and drug trafficking.
Keywords: Saúde; População ribeirinha; Satisfação dos usuários; Violência e acesso em saúde; CIENCIAS DA SAUDE::MEDICINA